Eficacia de bacterias epifíticas en la prevención del tizón foliar del maíz causado por Exserohilum turcicum - Sartori, Melina Victoria (2017)
Eight potential biological control agents (BCAs) were evaluated in planta in order toassess their effectiveness in reducing disease severity of northern leaf blight caused by Exserohilumturcicum. The assay was carried out in greenhouse. Twenty-six-day-old plants, V4 phenologicalstage, were inoculated with antagonists by foliar spray. Only one biocontrol agent wasused per treatment. Ten days after this procedure, all treatments were inoculated with E. turcicumby foliar application. Treatments performed were: C-Et: control of E. turcicum; T1: isolate1 (Enterococcus genus) + E. turcicum; T2: isolate 2 (Corynebacterium genus) + E. turcicum; T3:isolate 3 (Pantoea genus) + E. turcicum; T4: isolate 4 (Corynebacterium genus) + E. turcicum; T5:isolate 5 (Pantoea genus) + E. turcicum; T6: isolate 6 (Bacillus genus) + E. turcicum; T7: isolate 7(Bacillus genus) + E. turcicum; T8: isolate 8 (Bacillus genus) + E. turcicum. Monitoring of antagonistson the phyllosphere was performed at different times. Furthermore, the percentage ofinfected leaves and, plant and leaf incidence were determined. Foliar application of differentbacteria significantly reduced the leaf blight between 30---78% and 39---56% at 20 and 39 daysrespectively. It was observed that in the V10 stage of maize plants, isolate 8 (Bacillus spp.)caused the greatest effect on reducing the severity of northern leaf blight. Moreover, isolate 8was the potential BCA that showed more stability in the phyllosphere. At 39 days, all potentialbiocontrol agents had a significant effect on controlling the disease caused by E. turcicum.